In silico study of anti-tachycardia pacing efficacy optimisation through scar-targeted stimulation. (19th May 2022) - Qian, S; Connolly, A; Mendonca-Costa, C; Campos, F; Rodero, C; Whitaker, J; Rinaldi, C; Bishop, M
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Medical Research Council, UK Background: Anti-tachycardia pacing (ATP) is a reliable electrotherapy to painlessly terminate ventricular tachycardia (VT). However, ATP is often ineffective, particularly for fast VTs, which is often due to the inability of paced wavefronts to reach the re-entrant circuit, because of functional or anatomical barriers. It is thought that efficacy may be enhanced by optimised delivery closer to the re-entrant circuit driving the VT. Purpose: To quantitatively assess the dependence of ATP efficacy upon different delivery locations with respect to the re-entrant circuit. Methods: A cohort of 7 porcine ventricular infarct computational models were generated based on in vivo magnetic resonance imaging. Rapid-pacing protocols were applied to the cohort to induce VTs. Functional model parameters were adjusted to produce 73 episodes of sustained monomorphic VT, including 32 fast VTs (cycle length (CL)≤320ms) and 41 slow VTs (320ms-480ms). Burst ATP (2 sequences of 8 pulses at 88% of VTCL) was separately delivered from 3 locations proximal to the re-entrant circuit (along the RV septum), specifically within the critical isthmus (CI), and at the Exit and Entrance sites, along with 3 locations distal to the circuit (lateral/posterior LV), based on multipolar implanted devices with LV epicardial leads, constituting 438 virtual scenarios and efficacy compared (Fig A). Results: ATP efficacy was significantly higher for slow VTs than for fast VTs (65% vs 46%, P=0.00004) (Fig B). Separate analysis of slow VT cases revealed that delivering from distal locations to the re-entrant circuit was significantly more effective than delivering from proximal locations (72% vs 59%, P=0.04). However, for fast VT cases, the trend was reversed with proximal application (41%) being more effective than distal application (51%, P=0.15) (Fig B). Moreover, individual analysis on specific proximal locations revealed that in slow VT cases, delivering at the Exit site of VT was significantly less efficient than delivering at the Entrance site (46% vs 73%, P=0.01), with a similar (although non-significant) trend also being seen for fast VTs (44% vs 53%, P=0.5) (Fig C). Moreover, for fast VT cases, ATP delivery within the CI was overall the most effective (56%) than all other locations while this trend was not seen in slow VT cases. Conclusions: ATP delivery proximal to the re-entrant circuit improves efficacy in fast VTs, but less so in slow VTs, where delivering from distal sites is superior. Specifically, for fast VTs, ATP delivery within the CI is the most effective. This work suggests that real-time alteration in applied ATP delivery site choice in a multipolar device (guided by the sensed VT rate by the device prior to therapy delivery) may be beneficial. Combined with the state-of-art leadless pacing technology, this also provides a clinical opportunity for patient-specific ATP delivery configuration and programming.